The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1021/nl0805615
|View full text |Cite
|
Sign up to set email alerts
|

Method for Analysis of Nanoparticle Hemolytic Properties in Vitro

Abstract: Hemolysis (destruction of red blood cells) in vivo can lead to anemia, jaundice and other pathological conditions, therefore the hemolytic potential of all intravenously administered pharmaceuticals must be evaluated. Nanotechnology-derived devices and drug carriers are emerging as alternatives to conventional small-molecule drugs, and in vitro evaluation of their biocompatibility with blood components is a necessary part of early preclinical development. The small size and unique physicochemical properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
383
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 575 publications
(394 citation statements)
references
References 31 publications
7
383
2
2
Order By: Relevance
“…The UV-Vis spectra of the AgNPs band occur near 420 nm is shown in (Fig.2) indicating the formation of AgNPs due to reduction of silver ions by active molecules present in the seed extract. In accordance with previous literature studies were also reported by many researchers 17,18 . The brown color confirms that it was due to the reduction of Ag + which indicates the formation of AgNPs.…”
Section: Visual Observation and Uv-vis Spectroscopysupporting
confidence: 93%
“…The UV-Vis spectra of the AgNPs band occur near 420 nm is shown in (Fig.2) indicating the formation of AgNPs due to reduction of silver ions by active molecules present in the seed extract. In accordance with previous literature studies were also reported by many researchers 17,18 . The brown color confirms that it was due to the reduction of Ag + which indicates the formation of AgNPs.…”
Section: Visual Observation and Uv-vis Spectroscopysupporting
confidence: 93%
“…However, some particle interference due to haemoglobin precipitates adsorbed with the particles 321 on centrifugation has been reported, yielding a false negative result (Dobrovolskaia et al, 2008). 322…”
mentioning
confidence: 99%
“…Hemolysis of 510% and no change in globule size (p40.05) over 6 h in the serum stability study confirmed safety of the MEs for intravenous administration (Dobrovolskaia et al, 2008).…”
Section: Hemolysis and Serum Stabilitymentioning
confidence: 62%